The Origin of Late Cenozoic Magmatism in the South China Sea and Southeast Asia - Shengping Qian; Esteban Gazel; Alexander R. L. Nichols; Hao Cheng; Le Zhang; Vincent J. Salters; Jie Li; Xiaoping Xia; Huaiyang Zhou (Geochemistry, Geophysics, Geosystems, 2021)
Abstract Basaltic lavas sample recycled crustal materials from their mantle source. Constraining the location and residence time of these recycled materials in the mantle is critical to understand global mantle dynamics. In this study, we present new whole‐rock major and trace element abundances, Sr‐Nd‐Mo‐Os isotopes, water contents and He isotopes of volcanic glasses, U‐Pb ages of zircons, and compositions of melt inclusions, spinels and olivines from the South China Sea (SCS) seamounts lavas. These new data are compared with literature data from intraplate volcanism of similar age from Southeast (SE) Asia. The isotope data of late Cenozoic lavas from the SCS seamounts and SE Asia can be explained by mixing between enriched mantle 2 (EM2) and depleted mid‐ocean ridge basalt mantle components. Our data are consistent with the EM2 signature of late Cenozoic lavas derived from recycled young oceanic crust and sediments. The compositions of olivine phenocrysts indicate an olivine‐dominated (peridotitic) mantle source. There is currently no evidence for a high‐3He/4He mantle plume component beneath the SCS. Our results combined with geophysical data and plate reconstructions suggest that the late Cenozoic magmatism is related to the upwelling of instabilities from the mantle transition zone (MTZ) triggered by a stagnant slab. The SCS seamount lavas sample an enriched MTZ containing young recycled materials, consistent with regional past subduction. Our study provides additional evidence that storage and recycling of crustal materials in or near the MTZ is an important mechanism to develop global mantle heterogeneities sampled by intraplate volcanoes.